2022
DOI: 10.20882/adicciones.1400
|View full text |Cite
|
Sign up to set email alerts
|

Cambios en el consumo de alcohol en España de 1990 a 2019

Abstract: Cambios en el consumo de alcohol en España de 1990 a 2019 Changes in alcohol consumption in Spain between 1990 and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 41 publications
1
4
0
1
Order By: Relevance
“…In agreement with other studies [18,44], more than 90% of our BC survivors were moderately or completely adherent to limiting alcohol. This is in line with the decrease in alcohol intake observed in Spain at the beginning of the 20th century and the stabilization in the last decade [45]. Prevalence of compliance with this recommendation was lower in women with higher caloric intake, in line with the findings of the meta-analysis by Kwok et al, in which it was observed that the consumption of alcoholic beverages significantly increased food energy intake and total energy intake [46].…”
Section: Limit Alcohol Consumptionsupporting
confidence: 87%
“…In agreement with other studies [18,44], more than 90% of our BC survivors were moderately or completely adherent to limiting alcohol. This is in line with the decrease in alcohol intake observed in Spain at the beginning of the 20th century and the stabilization in the last decade [45]. Prevalence of compliance with this recommendation was lower in women with higher caloric intake, in line with the findings of the meta-analysis by Kwok et al, in which it was observed that the consumption of alcoholic beverages significantly increased food energy intake and total energy intake [46].…”
Section: Limit Alcohol Consumptionsupporting
confidence: 87%
“…Una de las cuestiones que puede explicar que las personas más jóvenes tengan un mayor consumo intensivo de alcohol es la asociación demostrada entre el binge drinking y el fenómeno "botellón", entendido como un grupo de personas, mayoritariamente jóvenes, que se reúnen para consumir alcohol en espacios públicos al aire libre. En el "botellón" se crea una situación donde factores como la presión por parte del grupo para beber alcohol, una mayor accesibilidad a bebidas más baratas y la creencia de efectos positivos, como que facilitará las relaciones sociales, pueden influir en la realización de un consumo intensivo de alcohol (Llamosas-Falcón, Manthey y Rehm, 2020;Teixidó-Compañó et al, 2019).…”
Section: Discussionunclassified
“…In favor of this hypothesis, whereas harmful alcohol consumption in New South Wales decreased by 5.5% between 2006 and 2015, Spain's per capita alcohol consumption remained stable between 2000 and 2006, followed by a decrease of 4.5% per year from 2006 to 2011 and a period of stability from 2011 onward. [34,35] Moreover, we accessed data based on the alcoholattributable mortality report of the National Drug Plan to describe the evolution of direct alcohol-attributable mortality in Spain during the study period 2001-2018 (Supporting Appendix S5). This revealed that while mortality seemed constant in females, mortality in males showed a sustained descent from 2010 to 2014, stabilizing from that year on, consistent with the alcohol consumption trends.…”
Section: Acceleration In the Decrease Of Hcc Mortality But Not For Ci...mentioning
confidence: 99%